Latency of Multifocal Visual Evoked Potential in Multiple Sclerosis: A Visual Pathway Biomarker for Clinical Trials of Remyelinating Therapies. Issue 3 (May 2021) - Klistorner, Alexander; Triplett, James D.; Barnett, Michael H.; Yiannikas, Con; Barton, Joshua; Parratt, John; You, Yuyi; Graham, Stuart L.
Abstract : Purpose: Acute focal demyelination is the characteristic feature of multiple sclerosis, with the majority of damaged axons undergoing limited remyelination and forming chronic lesions. Potential remyelinating agents are currently under development and there is therefore an urgent need for reliable in vivo biomarkers of remyelination. This study aimed to investigate potential changes in multifocal visual evoked potentials' (mfVEPs) latency in a cohort of relapsing–remitting multiple sclerosis (RRMS) patients. The potential sample size required for a remyelination-based clinical trial using different treatment effect sizes and the mfVEP latency as an outcome measure was also estimated. Methods: A total of 50 RRMS consecutive patients with no previous history of optic neuritis in at least one eye and 15 normal controls of similar age and gender composition were prospectively enrolled. Fifteen patients had a history of unilateral ON more than 12 months earlier, whereas 41 patients demonstrated optic radiations lesions on MRI at baseline. Most patients were on disease modifying therapy. A mfVEP was recorded at baseline and 12 months later. Results: At baseline, the mfVEP latency in RRMS patients was delayed compared with normal controls in both optic neuritis and nonoptic neuritis eyes. Latency delay was significantly correlated to optic radiation lesion volume ( R 2 = 0.38, P < 0.001). There was no significant latency change in multiple sclerosis patients' eyes or optic neuritis and nonoptic neuritis eyes over the follow-up period with latency remaining remarkably constant. This was despite the fact that 46 of 50 patients were on disease-modifying therapies, implying current treatments do not affect myelination in chronic RRMS cases. Sample size calculations to evaluate an additional or alternative remyelinating agent, based on a 40% treatment effect, revealed that a relatively small sample size (78 patients) would be required to demonstrate efficacy in future trials of remyelination therapies. Conclusions: Given its known sensitivity for latency changes and the stability found in this RRMS population, the mfVEP represents an ideal biomarker to assess the degree of latency recovery that may be achieved by remyelination in multiple sclerosis.